Pseudostenosis of the internal carotid artery in 3D time-of-flight MR angiography: effects of a magnetization transfer contrast pulse and metallic material - Naganawa, Shinji; Koshikawa, Tokiko; Sato, Kimihide; Katagiri, Toshio; Mimura, Takeo; Ishigaki, Takeo; Aoki, Ikuo (European radiology, 2003)
Pseudostenosis or pseudoocclusion of the internal carotid artery in 3D time-of-flight MR angiography has been reported to be caused by susceptibility artifacts due to the presence of a metallic foreign body in the subject's neck. We experimentally demonstrate that the use of a non-slice-selective magnetization transfer contrast (MTC) pulse increases the degree of pseudostenosis, whereas slice-selective MTC does not. Selective MR angiography demonstrating this phenomenon was also performed. We then report a case that exhibited this phenomenon. We conclude that the magnetic field inhomogeneity induced by metallic material causes the non-slice-selective MTC pulse to act as a local presaturation pulse. Selective MR angiography using this phenomenon can be applied on varieties of MR scanners from different vendors.